2012
DOI: 10.1212/wnl.0b013e31826d5f95
|View full text |Cite
|
Sign up to set email alerts
|

Deconditioning in patients with orthostatic intolerance

Abstract: Objective: To study the frequency and degree of deconditioning, clinical features, and relationship between deconditioning and autonomic parameters in patients with orthostatic intolerance. Methods:We retrospectively studied all patients seen for orthostatic intolerance at Mayo Clinic between January 2006 and June 2011, who underwent both standardized autonomic and exercise testing.Results: A total of 184 patients (84 with postural orthostatic tachycardia syndrome [POTS] and 100 without orthostatic tachycardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 14 publications
1
76
0
1
Order By: Relevance
“…11 As in all types of orthostatic intolerance, typical exacerbating factors include heat exposure, physical exertion, heavy meals, prolonged recumbency, menses, and drugs such as diuretics and vasodilators. 12 Classic Pathophysiology and POTS Subtypes Exaggerated postural tachycardia may reflect several pathophysiologically distinct mechanisms 2,4,6,8,9,[13][14][15][16] ( Table 1). Based on autonomic testing and plasma norepinephrine (NE) levels, POTS has been classified into several subtypes, including neuropathic and hyperadrenergic POTS 2,13 and, based on measurement of leg venous pressure and calf blood flow, as low-flow, high-flow, and normal-flow POTS.…”
Section: Pots As a Syndrome Of Orthostatic Intolerancementioning
confidence: 99%
See 1 more Smart Citation
“…11 As in all types of orthostatic intolerance, typical exacerbating factors include heat exposure, physical exertion, heavy meals, prolonged recumbency, menses, and drugs such as diuretics and vasodilators. 12 Classic Pathophysiology and POTS Subtypes Exaggerated postural tachycardia may reflect several pathophysiologically distinct mechanisms 2,4,6,8,9,[13][14][15][16] ( Table 1). Based on autonomic testing and plasma norepinephrine (NE) levels, POTS has been classified into several subtypes, including neuropathic and hyperadrenergic POTS 2,13 and, based on measurement of leg venous pressure and calf blood flow, as low-flow, high-flow, and normal-flow POTS.…”
Section: Pots As a Syndrome Of Orthostatic Intolerancementioning
confidence: 99%
“…The term orthostatic intolerance is used to describe a condition in which patients develop symptoms on standing or HUT but do not fulfill the heart rate criteria for the diagnosis of POTS. 4 The diagnostic criteria for orthostatic intolerance and POTS in adults are unsuitable for children and adolescents, and new criteria for these disorders in this age group have been recently proposed.5 POTS is more frequent in women (female:male ratio, 4.5:1), and most cases occur between the ages of 15 and 25 years. Up to 50% of cases have antecedent viral illness, and 25% have a family history of similar complaints.…”
mentioning
confidence: 99%
“…Here, we present frequencies of symptoms involving various organ systems as reported by a cohort of POTS patients. Th ere are multiple syndromes of orthostatic intolerance in which patients develop symptoms upon standing, but not all fulfi ll the diagnostic criteria of POTS (7). Th is heterogeneity contributes to the diagnostic and management challenges faced by patients and providers.…”
mentioning
confidence: 99%
“…In contrast, a recent retrospective study showed deconditioning in .90% of patients with POTS after upright exercise testing. 22 This discrepancy may reflect selection bias as well as differences in exercise protocols.…”
mentioning
confidence: 99%